Novel Fibrinogen Truncation with Deletion of Bβ Chain Residues 440-461 causes Hypofibrinogenaemia - Homer, Vivienne M.; Brennan, Stephen O.; Ockelford, Paul; George, Peter M. (Thrombosis and Haemostasis, 2002)
A 24-year-old male with hepatitis C was initially diagnosed with hypofibrinogenaemia during investigations prior to a liver biopsy. He had a low functional and gravimetric fibrinogen concentration of 1.0 mg/mL and DNA sequencing of all exons, exon-intron boundaries and promoter regions of the fibrinogen Aα, Bβ, and γ genes revealed a single heterozygous g→a mutation at nucleotide 8035 of the Bβ gene. This creates a premature stop at the Trp 440 codon and results in a 22-residue truncation of the Bβ chain. Analysis of purified plasma fibrinogen by SDS PAGE, reverse phase HPLC and ESI MS, however, failed to detect any of the truncated chains in the plasma fibrinogen. The non-expression of aberrant molecules was further confirmed by functional analysis, which revealed normal fibrin polymerisation. The principal structural feature of the independently folding βD domain is its five-stranded anti-parallel β sheet. The deletion here of residues 440 to 461 removes the second strand from this sheet structure and appears to impact on the viability of the nascent chain and its ability to be incorporated into mature fibrinogen molecules. The mutation does not however provoke the formation of hepatic inclusion bodies.
Keywords: Hypofibrinogenaemia; chain truncation; strand deletion; D domain; mass spectrometry